Mathematics Busy Board: Pelatihan kepada Ibu-Ibu di Posyandu Japan untuk Meningkatkan Pemahaman tentang Kemampuan Dasar Matematika dan Sensorik Motorik Anak di Usia Emas - Maharani, Swasti; Sanusi, Sanusi; Romandoni, Hendrisa Rizqie; Susanti, Vera Dewi; Andari, Tri; Prastyaningrum, Ihtiari (Universitas Tribhuwana Tunggadewi Malang, 2024)
The Golden Period is an essential period for children's growth and development. At this time, it is perfect if parents maximize their children's growth and development by training their children's sensory motor skills. Apart from that, fundamental mathematical skills such as recognizing numbers also need to be trained now. Based on the survey results in Ponorogo, parents still need clarification about how to train their children's sensory motor skills. In this context, the Mathematics Busy Board appears to be an exciting innovation that can improve children's basic mathematical and sensory motor skills in their golden age. This activity aims to provide knowledge or insight to mothers who have toddlers to optimize children's development, especially in basic mathematics and sensory-motor skills. The activity will occur at Posyandu Papaya, Japan Village, Jenangan District, Ponorogo Regency. The method used is that the team provides training or socialization about the importance of sensory-motor development and basic mathematical abilities. The results of the activity showed that there was an increase in the knowledge of mothers with toddlers about children's basic mathematical and sensory motor skills.ABSTRAKGolden Period merupakan masa penting bagi pertumbuhan dan perkembangan anak. Pada masa ini sangat baik apabila orang tua memaksimalkan tumbuh kembang anak dengan cara melatih sensorik motorik anak. Selain itu kemampuan matematika dasar seperti mengenal angka juga perlu mulai dilatihkan pada masa ini. Berdasarkan hasil survei di ponorogo, para orang tua masih kebingungan untuk melatihkan sensorik motorik ke anaknya. Dalam konteks ini, Mathematics Busy Board muncul sebagai inovasi yang menarik untuk meningkatkan kemampuan dasar matematika dan sensorik motorik anak di usia emas. Tujuan dari kegiatan ini yaitu untuk memberikan pengetahuan atau wawasan kepada ibu-ibu yang memiliki balita untuk mengoptimalkan perkembangan anak terutama pada kemampuan dasar matematika dan sensorik motoriknya.. Lokasi kegiatan berada di Posyandu Pepaya Desa Japan Kecamatan Jenangan Kabupaten Ponorogo. Metode yang dilakukan yaitu tim memberikan pelatihan atau sosialisasi tentang pentingnya perkembangan sensorik motorik dan kemampuan dasar matematika. Hasil kegiatan menunjukkan bahwa adanya peningkatan pengetahuan para ibu-ibu yang memiliki balita tentang kemampuan dasar matematika dan sensorik motorik anak.